2009
DOI: 10.4103/0250-474x.51953
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial activity of 5-imidazolinone derivatives

Abstract: Several 4-arylidene-2-phenyl-1-(2,4,5-trichlorophenyl)-1H-imidazol-5(4H)-ones (4a-q), N-(4-benzylidene-5-oxo-2-phenyl-4,5-dihydroimidazol-1-yl)-4-chlorobenzamides (5a-o) and N-(4-benzylidene-5-oxo-2-phenyl-4,5-dihydroimidazol-1-yl)-2,4-dichlorobenzamides (6a-m) were prepared. All newly synthesized compounds have been tested for their antibacterial activity against gram (+)ve and gram (−)ve bacteria and also on different strains of fungi. Introduction of OH, OCH3, NO2, Cl and Br groups to the heterocyclic frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…The study reported in this article is in continuation of the previous work aimed at synthesizing bio-active heterocyclic entities (Desai and Desai, 2005;Desai and Undavia, 1998;Desai and Undavia, 1996;Desai and Bhavsar, 2008;Desai and Saxena, 2008;Desai and Baldaniya, 2009). …”
Section: Introductionmentioning
confidence: 76%
“…The study reported in this article is in continuation of the previous work aimed at synthesizing bio-active heterocyclic entities (Desai and Desai, 2005;Desai and Undavia, 1998;Desai and Undavia, 1996;Desai and Bhavsar, 2008;Desai and Saxena, 2008;Desai and Baldaniya, 2009). …”
Section: Introductionmentioning
confidence: 76%
“…Anticonvulsant activity was determined against pentylenetetrazole-induced seizures in mice, 25-30 g of either sex 11,12,14 . The mice were divided into groups of five mice and keeping the group weight as near as possible.…”
Section: Determination Of Anticonvulsant Activitymentioning
confidence: 99%
“…Imidazolinone is an important scaffold possessing a spectrum of pharmacological actions, which includes anticonvulsant, antiparkinsonism and monoamino-oxidase inhibitory activities [7][8][9][10][11][12] . A careful scrutiny of structure activity relationship studies of anticonvulsant agents reported in literature indicates that ureido moiety is responsible for the anticonvulsant action [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it is known that the imidazolinone derivatives are associated with a wide range of therapeutic activities such as anticonvulsant (Godefroi & Platje, 1972), potent CNS depressant, (Harfenist et al, 1978). Recently some new imidazolinone derivatives have been reported as antimicrobial (Desai et al, 2009;Solankee et al, 2004), anticancer (Solankee et al, 2004) and L-DOPA prodrugs in the treatment of Parkinson's disease (Giorgionia et al, 2010). In view of these results and as continuation of our reaction mixture was filtered while hot to remove triethylamine hydrochloride salt and evaporated under reduced pressure till dryness and the remaining residue was triturated with ethanol (10 ml).…”
Section: Introductionmentioning
confidence: 99%